Calculation of Effective Permittivity of Mixtures During the Microwave Heating on the Chemical Reaction - Yang, Xiao-Qing; Huang, Ka-Ma; Yang, Li-Jun (Asian Journal of Chemistry, 2010)
For better application of microwaves heating in chemistry, the interaction between microwave and the chemical reactions needs for further studies. Usually, an effective permittivity can be used to describe the molecular polarization of the mixture in the reaction and consequently be used to calculate the transmission and absorption of microwave in the reaction mixtures. However, there is still a lack of the calculation method for the effective permittivity of mixtures under the microwave heating on the chemical reaction. Here, a simple method based on experimental results was employed to calculate the effective permittivity of mixture during the microwave heating on chemical reaction. To corroborate this method, two chemical reactions were employed. The calculated results of effective permittivity of the mixtures are in good agreement with the measured results. Using this method, the permittivity of reaction mixture decided by temperature and its composition can be obtained.